Preparation of polydimethylsiloxane-SiO2/PVDF-HFP mixed matrix membrane of enhanced wetting resistance for membrane gas absorption - Toh, M.J. (Elsevier B.V., 2020)
Membrane gas absorption (MGA) has been widely used to separate CO2 from gas mixture attributed to its high interfacial area. In order to secure high absorption flux, the pores of the membrane need to be non-wetted. Currently, hydrophobic membrane suffers from severe pore wetting over prolonged periods of operation. This has called for the enhancement of membrane hydrophobicity to suppress the tendency of pore wetting. In this work, highly hydrophobic PVDF-HFP membrane was synthesized using solvent additive i.e. polydimethylsiloxane-grafted-silica (PGS) via non-solvent induced phase separation. Results showed that mixed matrix membranes (MMMs) exhibited hierarchical structure composed of polymer spherulites due to delayed phase inversion. The embedment of nanoparticles in membrane matrix also contributed to the reduction of membrane's surface energy. As a result, MMMs achieved an improvement in wetting resistance with a water contact angle up to 149.87Â° at 3 wt of PGS nanoparticles. The CO2 absorption test using MEA as liquid absorbent showed that MMMs exhibited an enhancement in gas absorption flux owing to higher hydrophobicity. The CO2 absorption flux of pristine and MMMs was declined about 37 and 22, respectively during 150 h of operation. Â© 2020 Elsevier B.V.